Evaluation of unsulfated biotechnological chondroitin in a knee osteoarthritis mouse model as a potential novel functional ingredient in nutraceuticals and pharmaceuticals - Cimini, Donatella; Boccella, Serena; Alfano, Alberto; Stellavato, Antonietta; Paino, Salvatore; Schiraldi, Chiara; Guida, Francesca; Perrone, Michela; Donniacuo, Maria; Tirino, Virginia; Desiderio, Vincenzo; Rinaldi, Barbara (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis is a very disabling disease, which can be treated with both non-pharmacological and pharmacological approaches. In the last years, pharmaceutical-grade chondroitin sulfate (CS) and glucosamine emerged as symptomatic slow acting molecules, effective in pain reduction and improved function in patients affected by osteoarthritis. CS is a sulfated glycosaminoglycan that is currently produced mainly by extraction from animal tissues, and it is commercialized as pharmaceutical grade ingredient and/or food supplement. However, public concern on animal products derivatives, has prompted the search for alternative non-extractive production routes. Thus, different approaches were established to obtain animal-free natural identical CS. On the other hand, the un-sulfated chondroitin, which can be obtained via biotechnological processes, demonstrated promising anti-inflammatory properties in-vitro, on chondrocytes isolated from osteoarthritic patients. Therefore, the aim of this study was to explore the potential of chondroitin, in respect to the better-known CS, in an in-vivo mouse model of knee osteoarthritis. Results indicate that the treatment with biotechnological chondroitin, similarly to CS, significantly reduced the severity of mechanical allodynia in a MIA-induced osteoarthritic mouse model. A decreased cartilage damage and a reduction of inflammation- and pain-related biochemical markers were also observed. Overall, our data support a beneficial activity of biotechnological un-sulfated chondroitin in the osteoarthritis model tested thus suggesting BC as potential functional ingredient in pharmaceuticals and nutraceuticals with the advantage of avoiding animal tissue extraction.